The Transcendence of State-Sanctioned Violence and Christian Solidarity: East Timor and the End of the Indonesian Occupation - Hodge, Joel (Political theology, 2014)
This essay is concerned with the nature of the human experiences of transcendence and solidarity with particular reference to state-sanctioned violence and the non-violent resistance inspired by Christian faith. With research undertaken in East Timor, the essay identifies two different forms of transcendence—one marked by mob violence; and the other by ecclesial solidarity. It explores these forms of transcendence in the context of the statesanctioned executions in East Timor that occurred in 1999 after the populace voted for independence from Indonesia, which had brutally occupied the territory from 1975 to 1999. Through the story of a group that was to be executed, the essay explores the nature of state-sanctioned violence as structured by violent transcendence; and the Christian solidarity informed by a pacific transcendence located in the victimhood of Christ. The essay claims that the anthropological insights of René Girard provide an important lens to understanding the East Timorese experience, in which I argue that statesanctioned violence was resisted through the pacific transcendence located in Christ that awakened a consciousness of the victim.